Artificial intelligence: methodology, systems, and applications : 16th International Conference, AIMSA 2014, Varna, Bulgaria, September 11-13, 2014. Proceedings - Hitzler, Pascal; Krisnadhi, Adila A.; Kuznetsov, Sergei O.; Agre, Gennady (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 16th International Conference on Artificial Intelligence: Methodology, Systems, and Applications, AIMSA 2014, held in Varna, Bulgaria in September 2014. The 14 revised full papers and 9 short papers presented were carefully reviewed and selected from 53 submissions. The range of topics is almost equally broad, from traditional areas such as computer vision and natural language processing to emerging areas such as mining the behavior of Web-based communities.